Strategies to Improve Employee Performance Through Employee Engagement, Organizational Culture, Work Motivation, and Job Satisfaction on Employee Performance - Saing, Bungaran; Eprianto, Idel (Universitas Bangka Belitung, 2025)
This study uses a fit model to place work motivation as a mediator to analyze how organizational culture and employee engagement affect employee performance in Bekasi. This study closes the research gap and necessitates further testing to evaluate organizational culture's and employee engagement's impact on employee performance from other perspectives. Applying a fit mediation method and SEM, the research instruments utilized are a quantitative cross-sectional study and a questionnaire for Bekasi employees, demonstrating the significance of the variables. By placing work motivation and job satisfaction as fit mediators, the study gives empirical evidence that organizational culture and employee engagement have an impact on employee performance. The analysis's findings include positive guidance, especially in inspiring workers through active participation and constructive organizational principles that improve business performance.